IMPROVEMENT OF ECOLOGICAL CONCEPTS IN PRIMARY CLASS STUDENTS BASED ON INTEGRATION OF SCIENCES - Jurakul PANJIEV (Scholar Express Journal, 2023)
This article is written about the improvement of ecological concepts in elementary school students based on the integration of subjects. They combine different systems of knowledge, provide an opportunity to know the diversity of the phenomenon or process. Based on this knowledge, general concepts arise. The formation of interdisciplinary imaginations allows to use knowledge, to subordinate them to each other, to identify gaps in the boundaries of knowledge
Keywords: Class; learner; environmental; science